Intensified ChlVPP/ABVVP chemotherapy regimen and pegfilgrastim support in advanced Hodgkin lymphoma - Cocorocchio, E (Cancer Intelligence, 2010)
We present feasibility, toxicity and efficacy results of an intensified six-cycle ChlVPP/ABVVP regimen in advanced Hodgkin lymphoma (HL). From February 2004 to August 2007, 82 consecutive eligible patients were enrolled. According to the Hasenclever index, 64 patients (78%) were considered at low risk, 15 (18%) at intermediate and 3 (4%) at high risk. The most relevant toxicity was haematological: grade 3–4 neutropenia occurred in 32% of patients, grade 3–4 anaemia in 26% of patients. Severe infections and febrile neutropenia were observed in 8% of patients. With a median follow-up of 35 months (range 12–55), the three-year freedom from treatment failure (FFTF) and overall survival (OS) were 75% (95% CI 65%–86%) and 94% (95% CI 87%–99%), respectively. The intensified ChlVPP/ABVVP regimen in advanced HL is effective, does not seem to differ from standard regimens in terms of FFTF and OS and showed a favourable toxicity profile.